Characterization of thermobifida fusca cutinase-carbohydrate-Binding modube fusion proteins and their potential application in bioscouring - Zhang, Yao (2010)
Cutinase from Thermobifida fusca is thermally stable and has potential application in the bioscouring of cotton in the textile industry. In the present study, the carbohydrate-binding modules (CBMs) from T. fusca cellulase Cel6A (CBMCel6A) and Cellulomonas fimi cellulase CenA (CBMCenA) were fused, separately, to the carboxyl terminus of T. fusca cutinase. Both fusion enzymes, cutinase-CBMCel6A and cutinase-CBMCenA, were expressed in Escherichia coli and purified to homogeneity. Enzyme characterization showed that both displayed similar catalytic properties and pH stabilities in response to T. fusca cutinase. In addition, both fusion proteins displayed an activity half-life of 53 h at their optimal temperature of 50°C. Compared to T. fusca cutinase, in the absence of pectinase, the binding activity on cotton fiber was enhanced by 2% for cutinase-CBMCel6A and by 28% for cutinase-CBMCenA, whereas in the presence of pectinase, the binding activity was enhanced by 40% for the former and 45% for the latter. Notably, a dramatic increase of up to 3-fold was observed in the amount of released fatty acids from cotton fiber by both cutinase-CBM fusion proteins when acting in concert with pectinase. This is the first report of improving the scouring efficiency of cutinase by fusing it with CBM. The improvement in activity and the strong synergistic effect between the fusion proteins and pectinase suggest that they may have better applications in textile bioscouring than the native cutinase.